Analisis Penerapan Profil Pelajar Pancasila dalam Pembentukan Karakter Peserta Didik di SDN 23 Talang Babungo - Zulfitria, Zulfitria; Gusmaletri, Gusmaletri; Gusnita, Fitria; Anisa, Mela; Triana, Mamy (Lembaga Intelektual Muda (LIM) Maluku, 2024)
According to the Pancasila Student Profile Project, one of the primary features of the Merdeka curriculum is the autonomy of students in cultivating their character and soft skills. Through extracurricular and intracurricular activities that emphasize developing students' character in their everyday lives, the school culture implements the Pancasila student profile. The purpose of this study is to ascertain how the Pancasila student profile is used to help students at SDN 23 Talang Babungo develop their character. This research employs a qualitative methodology. Direct observation of grade V students and in-depth interviews with the principal, instructors, and students were used to gather data. Techniques for gathering data include documentation, interviews, and observation. Data reduction, data presentation, and verification were the phases of descriptive and interpretative data analysis. The study's findings demonstrate that using the Pancasila student profile enables students to incorporate Pancasila ideals into their daily lives, boosting their motivation, engagement, and critical thinking abilities. Additionally, education fosters the development of social skills in kids, such collaboration and environmental awareness. Teachers must consistently adopt techniques with diverse innovations to tackle the issues that occur in the school. This will ensure that the Pancasila student profile is implemented easily and that the aim of building students' character